Jejak Pendidikan Primer dalam Tantra - I Putu Suweka Oka Sugiharta (Jurnal Pendidikan Agama, 2023)
In the course of Tantra found traces of learning from very ancient times. Of course, the journey is accompanied by success and failure. This dynamic process has made Tantra still have loyal adherents to this day. Apart from showing maturity, the Tantric method also displays natural honesty. Every human being needs a natural way of learning. Because education that is too artificial seems to lead individuals to dehumanization. In forming a complete human being, the most primary education is needed. This study aims to describe the advantages of Tantric educational values ​​which are often misinterpreted. This research used qualitative approach which literature as a basis for descriptions and narratives to get meaning. The results of the study, primary education in Tantra seeks to achieve holisticity, serve gender determinism, anticipate future chaos, and interpret masculine and feminism aspects as strengths. The conclusion of this study is that the scope of Tantric education is much wider than the scope of modern education which only includes the family education